Symmetries in the physics of strongly correlated electronic systems - Mancini, F.; Avella, A. (Condensed Matter Physics, 1998)
Strongly correlated electron systems require the development of new theoretical schemes in order to describe their unusual and unexpected properties. The usual perturbation schemes are inadequate and new concepts must be introduced. In our scheme of calculations, the Composite Operator Method is possible to recover through a self-consistent calculation, a series of fundamental symmetries by choosing a suitable Hilbert space.